2016
DOI: 10.1111/dpr.12159
|View full text |Cite
|
Sign up to set email alerts
|

The future of small farms in Asia

Abstract: Journal articleIFPRI3; ISI; C Improving markets and tradeMTIDP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 41 publications
0
40
0
Order By: Relevance
“…IFAD (2013) reported that supporting smallholders financially could help to lift more than 5% of people in Asia out of poverty. However, the production efficiency of small farms in many Asian countries has decreased relative to large farms, and hence they are likely to lose comparative advantage (Otsuka, Liu, and Yamauchi 2016).…”
Section: Control Variablesmentioning
confidence: 99%
“…IFAD (2013) reported that supporting smallholders financially could help to lift more than 5% of people in Asia out of poverty. However, the production efficiency of small farms in many Asian countries has decreased relative to large farms, and hence they are likely to lose comparative advantage (Otsuka, Liu, and Yamauchi 2016).…”
Section: Control Variablesmentioning
confidence: 99%
“…Due to the limiting effect of sharecrop on the tenant's efforts, the "Marshall's conventional theory" considers sharecrop as incompetent, unless production risks and farmer pose more risk aversion [4,5]. Reforms of agriculture land, which offer assurance (secure rights) of farmland, may enhance productivity [6].…”
Section: Introductionmentioning
confidence: 99%
“…In general, aquaculture has the potential to reduce poverty directly or indirectly (De Janvry & Sadoulet, ; Edwards, ; Kassam, ) not only through establishing and strengthening food consumption linkages, but also through “income linkages” and “employment linkages” (Ahmed & Lorica, ; Belton, Ahmed & Murshed‐e‐Jahan, ; Belton et al., ). Reducing poverty in low‐income countries through smallholder development remains compelling where the majority of people live in rural areas, and agriculture remains the largest single source of employment (Hazell, Poulton, Wiggins & Dorward, ; Otsuka, Liu & Yamauchi, ; Wiggins, Kirsten & Llambi, ). In Bangladesh, direct benefits from aquaculture are largely determined by the availability and access to assets and thus, the capacity of poor people to benefit from aquaculture occurs mostly through indirect food consumption linkages (Belton & Little, ; Bogard et al., ; Roos, Wahab, Chamnan & Thilsted, ; Toufique & Belton, ).…”
Section: Introductionmentioning
confidence: 99%